2011
DOI: 10.1016/j.tics.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Memory distortion: an adaptive perspective

Abstract: Memory is prone to distortions that can have serious consequences in everyday life. Here we integrate emerging evidence that several types of memory distortions – imagination inflation, gist-based and associative memory errors, and post-event misinformation – reflect adaptive cognitive processes that contribute to the efficient functioning of memory, but produce distortions as a consequence of doing so. We consider recent cognitive and neuroimaging studies that link these distortions with adaptive processes, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
304
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 414 publications
(348 citation statements)
references
References 96 publications
(124 reference statements)
20
304
0
6
Order By: Relevance
“…Indeed, recent treatments of "false memory" have begun to attribute many distortions to the operation of adaptive processes, rather than to some flaw inherent in the system (for recent review see Schacter, Guerin, & St. Jacques, 2011). This is not to say that memory content is unconstrained.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent treatments of "false memory" have begun to attribute many distortions to the operation of adaptive processes, rather than to some flaw inherent in the system (for recent review see Schacter, Guerin, & St. Jacques, 2011). This is not to say that memory content is unconstrained.…”
Section: Discussionmentioning
confidence: 99%
“…That the human memory system is a fallible system is without question (e.g., see Howe, 2011a;Schacter, Guerin, & St. Jacques, 2011). Although a number of paradigms have established that memory is a powerful yet reconstructive system that is prone to error, it is perhaps the Deese/Roediger-McDermott (DRM) paradigm that has provided us with the quintessential evidence for this in terms of spontaneous false memory illusions (Deese, 1959;Roediger & McDermott, 1995).…”
Section: True and False Memoriesmentioning
confidence: 99%
“…However, recent research has demonstrated that the production of false memories need not always have negative implications (see Howe, 2011a;Newman & Lindsay, 2009;Schacter et al, 2011). For example, research has demonstrated that false memories (i.e., DRM critical lures) are capable of priming performance on implicit memory tasks such as word-stem completions (McDermott, 1997;McKone & Murphy, 2000) or anagrams (Lövdén and Johansson, 2003).…”
Section: True and False Memoriesmentioning
confidence: 99%
“…Semantic representations are capable of capturing important structural features of the world at many different levels of abstraction, which allows for rapid and flexible responses to a diverse array of environmental challenges. This preexisting knowledge structure guides ongoing cognition, which usually aids performance, but under some circumstances can lead us into error (1)(2)(3). A striking example is the widely studied DRM (Deese, Roediger, and McDermott) false-memory illusion (4,5).…”
mentioning
confidence: 99%